EXISTING LEGAL PROVISIONS IN INDIA FOR THE PROTECTION OF THE ENVIRONMENT: A STUDY - Jethani, T.M.; Naidu, S. T. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
No constitution deals, with matters such as environmental protection, because any constitution contains only the rules of laws concerning the power structure, allocation, and manner of exercise. Besides Indian constitution is already a bulky document and brevity is the character of an ideal constitution. Hence from the point of view of the principles of constitutional law as well as the length of the constitution, it was impossible to have any Such Provision Safeguarding the healthy environment. Therefore, till the Subsequent amendment the constitution text of India was without any specific provision for the protection and promotion of the environment. However, the seeds of such provision could be seen in Article 47 of the constitution which Commands the state to improve the slandered of living and public Health. To fulfill this Constitutional goal, the state must provide a pollution-free environment. To afford better protection for the environment, the constitution was amended. The amended provided the following Article 48-A: By the constitution (42nd Amendment) Act, protection and improvement of environment and safeguarding of forest and wildlife. The State shall endeavour to protect and improve the environment and safeguard the forest and wildlife of the country. Article 51-A (g) – By Constitution (42nd Amendment) Act, 1976 It shall be the duty of every citizen of India to protect and improve the natural environment including forests—lakes, rivers and wildlife and to have compassion for living creatures.